Tofacitinib Facilitates the Expansion of Myeloid‐Derived Suppressor Cells and Ameliorates Arthritis in SKG Mice. Issue 4 (April 2015) - Nishimura, Keisuke; Saegusa, Jun; Matsuki, Fumichika; Akashi, Kengo; Kageyama, Goichi; Morinobu, Akio
Abstract : Objective: Myeloid‐derived suppressor cells (MDSCs) are a heterogeneous population of cells that have the ability to suppress T cell responses. The aim of this study was to evaluate the effects of the JAK inhibitor tofacitinib on MDSCs in a mouse model of rheumatoid arthritis. Methods: Arthritis was induced in SKG mice by zymosan A (ZyA) injection. MDSCs isolated from the bone marrow (BM) of donor SKG mice with arthritis were adoptively transferred to recipient mice with arthritis. In a separate experiment, tofacitinib was administered to arthritic SKG mice subcutaneously via osmotic pump, in some cases followed by injection of an anti–Gr‐1 monoclonal antibody (mAb). BM cells from untreated mice were cultured for 5 days with granulocyte–macrophage colony‐stimulating factor, with or without tofacitinib, and then analyzed by flow cytometry. Results: The numbers of MDSCs and polymorphonuclear MDSCs (PMN‐MDSCs) were significantly increased in the spleens of SKG mice following ZyA injection. Adoptive transfer of MDSCs to recipient arthritic mice reduced the severity of arthritis compared to that in untreated control mice. Treatment with tofacitinib also ameliorated the progression of arthritis in SKG mice and induced significantly higher numbers of MDSCs and PMN‐MDSCs in the BM of these animals. Furthermore, administration of an anti–Gr‐1 mAb reduced the antiarthritic effect of tofacitinib in SKG mice. In vitro, tofacitinib facilitated the differentiation of BM cells to MDSCs, and inhibited their differentiation to dendritic cells. Conclusion: Tofacitinib facilitates the expansion of MDSCs and ameliorates arthritis in SKG mice.